ANALISIS SISTEM PEMERINTAHAN DAN PERLINDUNGAN HUKUM TERHADAP HAK ULAYAT MASYARAKAT ADAT BADUY - Tuasalamony, Adzra Ardelia (Jurnal Hukum Statuta, 2024)
The government system owned by the Baduy community is different from the government system, especially the village level government system that applies nationally which is regulated in Law Number 23 of 2014 concerning Regional Government and Law Number 6 of 2014 concerning Villages. The aim of this research is to examine the governance system of the Baduy traditional community and the legal protection of the customary rights of the Baduy traditional community. This research uses normative legal research which uses normative case studies, which are the results of legal actions. The Baduy community has its own system of government called kembanguh karuhun with three traditional leaders or better known as Puun with different regional positions (tangtu), namely, Cibeo, Cikartawana, and Cikeusik. The Baduy and Kasepuhan indigenous communities make their living as farmers with communal land ownership (ulayat rights) which are regulated by customary orders, therefore the Regent of Lebak ratified Lebak Regency Regional Regulation Number 32 of 2001 concerning Protection of the Customary Rights of the Baduy Community.